(untitled) (Agroindustrial Science, 2022)
The search for potential solutions to treat wastewater and provide added value motivate the objective of this study, which was to evaluate the efficiency and performance of Microbial Fuel Cells (MFC) in generating bioelectricity from the treatment of effluents from a pig farm, considering its performance with and without the use of inoculum. Three double chamber biocells were built and two treatments were implemented for 13 days with hourly voltage monitoring. In the first treatment, the autochthonous microorganisms of the wastewater were used and in the second, bovine manure was used as a source of inoculum. The effluent presented low biodegradability (BOD5 / COD = 0.22), in addition, removals greater than 80% and 67% were achieved for COD and BOD5 respectively, attributed first to the sedimentation of the effluent solids. The electrical parameters were very low compared to other investigations, reaching an average voltage lower than 200 mV and the coulombic efficiency lower than 0.1%. Statistically the treatments did not have significant differences in the removal of COD and BOD5, the mean voltage and coulombic efficiency. Finally, it was possible to generate bioelectricity but at a very low efficiency, which makes it important to investigate how to optimize the process.